2011
DOI: 10.1186/1471-2407-11-292
|View full text |Cite
|
Sign up to set email alerts
|

Distinct distribution and prognostic significance of molecular subtypes of breast cancer in Chinese women: a population-based cohort study

Abstract: BackgroundMolecular classification of breast cancer is an important prognostic factor. The distribution of molecular subtypes of breast cancer and their prognostic value has not been well documented in Asians.MethodsA total of 2,791 breast cancer patients recruited for a population-based cohort study were evaluated for molecular subtypes of breast cancer by immunohistochemical assays. Data on clinicopathological characteristics were confirmed by centralized pathology review. The average follow-up of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
61
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 35 publications
22
61
5
Order By: Relevance
“…The luminal A subtype was the most common cancers. This results were similar with others (Perou et al 2000;Sorlie et al, 2003;Milikan et al, 2008;Jia et al, 2010;Su et al, 2011;Najafi et a., 2012, Chuthapisith et al, 2012. Different result was reported …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The luminal A subtype was the most common cancers. This results were similar with others (Perou et al 2000;Sorlie et al, 2003;Milikan et al, 2008;Jia et al, 2010;Su et al, 2011;Najafi et a., 2012, Chuthapisith et al, 2012. Different result was reported …”
Section: Discussionsupporting
confidence: 92%
“…The luminal A subtype was significantly higher among 70 years old women, early stage, small size and low grade tumors, and it is reported to have longer survival rate compared to the non luminal one. The triple negative/basal-like subtype was significantly correllated with familial breast cancers (Su et al, 2011). Another research in China found that luminal A cancers have the best prognosis, whereas Her-2+ cancers have the poorest (Jia et al, 2014).…”
Section: Clinicopathological Features Of Indonesian Breast Cancers Wimentioning
confidence: 93%
“…The knowledge about periods of risks and common site of disease relapse could be used as a guide for focusing on clinical history and physical exams during the follow up visits and screening tests which provide the most information. Mean age of diagnosis in our study was 47.9±9.6 which was lower comparing to study of Su et al (2010) and Kadivar et al (2012) with a mean age of 53±10.4 years old at the time of diagnosis but Bennis et al (2012) similar to Tunisian study in which the mean age of diagnosis was reported 46.8±12 and Haghighat et al (2012) was higher comparing to Iranian study with a mean age of 45.9±10.5. In our patients 9% were under 35 years old and 63.5% were over 50 years old,similar to other Iranian study, patients under 35 years old were 12% and patients over 50 years old were 42% (Kadivar et al, 2012), with regard to study of Webster et al (2008) patients under 35 years old were 6.2% and patients over 50 years old were 37.8% (Webster et al, 2008), our patients had breast cancer at a younger age,possibily due to ethnic and genetic differences.…”
Section: Discussioncontrasting
confidence: 72%
“…Based on a high degree of heterogeneity, recently these tumors classify according to molecular characteristics (Perou et al, 2000;Sorlie et al, 2003;Viale, 2012). In the literature several studies have shown that triple negative (ER, PR and HER2 negative; basal like type) and HER2 subtypes were associated with poor prognosis compared with the luminal A subtype (Parise et al, 2009;Zhao et al, 2009;Su et al, 2011;Lv et al, 2011;Rao et al, 2013),. In the present study, positive HER 2 (IHC 3+) and negative ER, PR and HER2 (positive with CK 5/6, basal like type) were associated with high NLR while positive ER and PR related with lower NLR.…”
Section: Discussionmentioning
confidence: 99%